Perceptions, evidence and prevention of STIs among students from two reference high schools in the city of Paudalho/PE (Research, Society and Development, 2023)
Sexuality, which is awakened at the stage of puberty, is an inherent aspect of being human. From this period, physical and psychosocial changes occur. Thus, the absence of educational guidelines regarding this phase lead to the recurrence of the spread of sexually transmitted infections (STIs). In this sense, the present study aimed to evaluate, through a questionnaire, the understanding and prevalence of STIs among students of the EREM Confederação do Ecuador, located in Paudalho, PE, in order to obtain information to design and carry out educational interventions. The evaluation found that, although only 15.6% of the students consider they have a low level of knowledge about sexuality, 34.8% of the students consider they do not understand about STIs and AIDS. Furthermore, although 0.5% of students answered “yes” to the prevalence of STIs between the period 2020 to 2021 and 1.1% answered “maybe”, 10.3% of students answered that they may have had symptoms associated with STI's (changes in the genitalia: wounds, warts, secretions, different colored fluid) and 5.7% responded that they actually had these changes. Therefore, despite the ease of access to information from the development of the internet and social networks, ignorance about sexuality and STI prevention is still present, due to the absence of control and guidance regarding the bias of disseminated information and seen in these social tools.